CONDITIONS OF MARITIME METEOROLOGY AND OCEANOGRAPHY IN THE VICINITY OF KOTOK ISLAND, SERIBU ISLANDS: APRIL 2011 - Atika Lubis; Mira Yosi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Meteorological data measurement by an Automatic Weather Station (AWS) were carried out at the pier of Kotok Island for East Monsoon period on April 2011 to obtain the changes phenomenon of maritime meteorological parameter and their correlation with the changes of oceanographic condition in shallow waters area and its surrounding. The measurement consists of surface wind parameter, air temperature, humidity, air pressure, and oceanographic data observations such as batimetry, tide, sea current, sea surface temperature, and salinity distributions. Result of maritime meteorological assessment obtained from previous reports (1980, 1998, and 2001) showed that the changes of the maximum air temperature were relatively significant. Furthermore, the air pressure data at the sea surface increased approximately 1.3 mBar. Nevertheless, other meteorological data seemed to be less significant in changes, but indicated a strong correlation with the pattern of tidal current and propagated waves to the shoreline. The changes of oceanographic parameter in the shallow water area were triggered the sedimentation processes, so that the coral reef growth might be decreased.Keywords: Maritime meteorology, oceanographic parameter, flat coral reef